Determination of the optimal extractant for the extraction of biologically active substances of Sophora Flower–buds - Kriukova, A.; Bezruk, I; Konovalenko, I. (Annals of Mechnikov's Institute, 2020)
Introduction. According to the market products based on Sophora japonica L., extraction of biologically active substances, flavonoids in particular, is carried out with ethanol in a concentration 50–70%. However, in recent years, in literature data have appeared the information that the use of water–ethanol solutions is not effective for the extraction of biologically active substances and contributes to the release of a large amount of ballast substances. An alternative is to use surfactant–based extractants. In relation to Sophora Flower–buds, these questions have not been investigated, which determines the relevance of research on the selection of the optimal extractant. Material & methods. The object of the research is Sophora Flower–buds, harvested in 2018 during the budding period. The definition of quality indicators was carried out in accordance with the requirements of the State Pharmacopoeia of Ukraine. Results & discussion. Determination of Sophora Flower–buds technological parameters was conducted: the degree of grinding of herbal materials, specific mass, bulk density, bulk weight, porosity, permeability and free volume of the layer. The obtained data on the technological properties of the herbal material used to develop an optimal method for extracting, predicting and standardization of the quality of extracts. Studied one of quality indicators, that indicates a rationally selected extractant is “Determination of dry residue of extracts”. Also was carried out research a comparative evaluation of the flavonoids content in the extracts obtained. Quantitative determination of the sum of flavonoids was performed by spectrophotometric method according to the SPhU 2.1 method «Sophora Flower–buds». The data obtained indicate that the highest values of dry residue and maximum amount of flavonoids were obtained during the extraction for two to three hours using ethanol 50 % and sodium lauryl sulfate solution 2.5 % as the extractant. Content flavonoid compounds of different chemical composition Sophora Flower–buds can affect biological activity. Therefore, for a more objective evaluation of the extracting ability of the proposed extractants were conducted studies of antiradical activity. Research of the antiradical activity of Sophora Flower–buds showed that the maximum value of TEAC is exhibited by such agents as ethanol 50 % and sodium lauryl sulfate solution 2.5 %. The data obtained confirm that the antiradical activity depends on the quantitative content of flavonoids in the studied samples of Sophora Flower–buds. Conclusion. The research of possibility of using surfactants for the extraction of biologically active substances from Sophora Flower–buds was conducted. It is found that the best extractive ability to Sophora Flower–buds flavonoids have extractants: ethanol 50 % and sodium lauryl sulfate solution 2.5 %, which have virtually the same quality indicators: dry residue 8.81±0.37 and 8.54±0.45; the content of the sum of flavonoids 8.75±0.01 и 8.43±0.03. The study of antiradical activity in Sophora Flower–buds extracts was conducted for the first time. Maximum values are obtained in extracts by extraction over two hours using ethanol 50 % sodium lauryl sulfate solution 2.5 %. The data presented can be used in research on the development of Sophora Flower–buds herbal medicinal products in the various dosage form.